Percutaneous vertebropalsty at traumatic vertebral fractures - Kushchayev, S. V. (Ukrainian Neurosurgical Journal, 2008)
Vertebral traumatic fracture treatment is an actual problem of the modern neurosurgery. The article is dedicated to surgical treatment of uncomplicated compressive fractures, using percutaneous vertebroplasty method. The results of 26 patients treatment, suffered from traumatic thoracolumbar vertebral fractures were analyzed. High efficacy and safety of this method was shown.